Preventing COVID-19 with Chinese Medicine: Concepts and Suggestions - Shelley Ochs (Chinese Medicine and Culture)
The category of “epidemic diseases” is discussed extensively in the literature of traditional Chinese medicine, however it is often overlooked in modern Chinese medicine education precisely because population-level prevention and treatment do not fit easily into the dogma that individualized herbal formulas “based on patterns identified” is the primary mode of clinical reasoning in Chinese medicine. In the recent COVID-19 epidemic, the contingencies of treating large numbers of patients meant that it was not possible to provide “one prescription for each patient.” In fact, four categories of patients were sometimes given the same formula: mild and moderate confirmed cases, close contacts of confirmed cases, and suspected cases. The lines between prevention and treatment, along with clear demarcations between individual and population-level immunity, were blurred in the mist of the urgent imperative to provide what could reasonably be expected to be effective. Lessons from the large-scale participation of Chinese medicine in the COVID-19 public health crisis are relevant for the global community of Chinese medicine practitioners and may provide insights into how future epidemics could be addressed in the absence of effective vaccines or pharmaceuticals.